Anti-statist development? Growth, economic concentration, and segmented welfare in Chile - Jorge Atria (economic sociology. perspectives and conversations, 2024)
The modern capitalist revolution in Chile - the moment when the economic liberalism project was established as a stage prior to the Reagan and Thatcher governments, generating a radical break with the previous model (Gárate 2012) - immediately provoked a strong discussion on the implicit idea of development. Whether due to the profound transformation in the coordination between the state and the market, the various reforms in social areas, or the increase in economic concentration, it introduced a set of ideas on how development should be understood and, therefore, how the economy should set the standard for thinking about a better future for Chile.
Keywords: 300